Koncepcja monomitu w muzealnictwie narracyjnym - Eder, Mateusz (Studia Europaea Gnesnensia, 2024)
The aim of this article is to discuss the concept of monomyth, conceived by Joseph Campbell and elaborated using a different approach by Christopher Vogler, as well as its applicability in the field of contemporary museology and exhibitions. Specifically, the concept – with its recurring pattern of the Hero’s Journey – is examined in terms of what is known as narrative museology. The author also reflects on the essence of narrative museology as such, as well as analyzes the possibilities for monomyth to be used in creating a museum experience.